Aggressiveness of Indonesia Triple Negative Breast Cancer Driven by Programmed Death Ligand-1 and Tumor Microenvironment - Sari, Dianidya Kumandang; Fitri Hapsari , Rr. Ayu; Ariany, Devy; Sakaraga, Deamon (Faculty of Medicine, UIN Syarif Hidayatullah Jakarta, 2025)
Background: Triple-negative breast cancer (TNBC) is one of the most aggressive breast cancer subtypes in Indonesia. The expression of PD-L1 1 and TME characteristics play essential roles in both immune system avoidance and medical treatment results. The Indonesian medical field lacks a comprehensive analysis of local TNBC research data because new studies continue to emerge. Methods: The research followed PRISMA guidelines and PECO framework for analysis. A total of 22 records were identified; 10 studies met eligibility, and 6 studies were included in the final synthesis. Results: The studies showed a wide range of PD-L1 expression in tumor cells, from 21% to 93.5%, depending on antibody clone (SP142, SP263, 22C3) and scoring threshold. The studies showed that most tumors had high-grade characteristics between 42% and 88% while displaying high proliferative rates with Ki-67 ≥20% in more than 80% of cases. The three most common metastasis locations in patients were the lungs, bones and then the brain. The survival rates of patients improved when their CD8/CD163 and CD4/FOXP3 ratios increased. The survival outcomes of patients worsened when their PD-L1 expression levels or mRNA expression increased. Conclusion: Indonesian TNBC shows aggressive pathological characteristics with variable PD-L1 expression and diverse tumor microenvironments. PD-L1 alone does not provide consistent prognostic value and is best interpreted together with immune-cell ratios and TIL density. Establishing standardized biomarker evaluation and adopting immune-based molecular classification could improve the precision of immunotherapy strategies in Indonesia. Keywords:Triple-negative breast cancer, PD-L1, tumor microenvironment, immune ratios, metastasis, Indonesia